2020
DOI: 10.7759/cureus.11012
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Modified Makuuchi Incision for Surgical Management of Complex Renal and Adrenal Lesions

Abstract: Bokka et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, for large kidney tumors or surgeries in need of the manipulation of other organs such as the liver, pancreas, and spleen, other approaches may be required. 3 There have been some advantages described in the literature for MMI. In their study of 144 cases, Pandit et al showed that the MMI provided many operative ergonomics and less postoperative pain according to thoracoabdominal and inverted T incision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for large kidney tumors or surgeries in need of the manipulation of other organs such as the liver, pancreas, and spleen, other approaches may be required. 3 There have been some advantages described in the literature for MMI. In their study of 144 cases, Pandit et al showed that the MMI provided many operative ergonomics and less postoperative pain according to thoracoabdominal and inverted T incision.…”
Section: Discussionmentioning
confidence: 99%
“…As well, its use in adrenal and renal surgery is increasing. 3,4 This study aimed to evaluate the postoperative pain, incisional hernia, and cosmetic satisfaction of patients who underwent renal surgery with this technique.…”
Section: Anah Tar Ke LI Me Ler: Böbrek Cerrahisi; Makuuchi; Ağrı; Her...mentioning
confidence: 99%
“…Patients receiving conventional open hepato-biliary surgeries, among others, were particularly vulnerable to wound pain since they usually present with multiple comorbidities and are left with a large incision [ 8 ]. The most frequently used surgical incision for open liver resection is modified Makuuchi incision, which commences from xiphoid to about one to two centimeters above the umbilicus, and then extends laterally to the right [ 9 , 10 , 11 , 12 ]. According to the ERAS society, there is clinical equipoise in postoperative pain control for open liver surgery [ 13 ].…”
Section: Introductionmentioning
confidence: 99%